Impact of seed maturity and post harvest treatment on seed quality, germination performance and early seedling development of three soybean (Glycine max L. Merr.) varieties - Mahmood, Ali Imad (2018)
Soybean is one of the major crops in United State of America, Brazil and China. Unfavorable tropical climate such as high temperature and high relative humidity give the big impact on its production. In addition, storage condition also influences its seed quality and germination performance. This study aimed to study the impact of current practice on the seed quality, germination performance and longevity of three varieties of soybean seed which are AGS190, Cikurai and Willis that harvested at different maturity stages, seed drying and storage conditions. Seeds were planted in Ladang 2, Faculty of Agriculture, Universiti Putra Malaysia. The experiment was designed with the combination of two factors (varieties and maturity stages) and arranged in a complete randomized design (CRD) with three replicates. Data were analyzed using SAS software window version 9.4. Two-way analysis of variance (ANOVA) at p=0.05 was used to determine the different between parameter studied and followed by Least Significant Difference (LSD) at p=0.05 for mean comparison. In experiment 1, seeds were harvested at three maturity stages (R6-full seed; R7- physiological maturity; and R8-full maturity). The internal seed properties (moisture content and electrical conductivity), germination performance and early seedling growth were measured. The lowest seed quality is found at R6 due to the highest moisture content and electrical conductivity (2x higher than R7 and R8), as a result, the germination performance and early seedling growth is significantly lower. R7 is the ideal harvesting stage for all soybean varieties due to the germination performance more than 90%. AGS190 showed the lowest on the parameter studied compared to Cikurai and Willis. In experiment 2, the effects of ultradry and different storage condition on the seed quality, longevity and early seeding growth were compared. Seeds were divided into non-ultra-dry and ultra-dry seeds and stored separately in room temperature (25-30 oC with relative humidity 65-70%) and cold room storage condition (10 oC with relative humidity 80-85%) for 12 months. Type of seed drying and storage condition had the significant effect (ANOVA, P<0.05) on antioxidant enzymes activity (SOD and CAT), deterioration process, germination performance and early seedling growth of soybean seeds. The deterioration process is slow in ultradry seed storage (moisture content 4%) compared with non-ultra-dry seed storage (moisture content 12%). The results showed that cold room storage and ultra–dry method is recommended for maintain the seed longevity due to low MDA content and EC. The recommended duration for seed storage is less than 4 month for maintain the longevity of soybean seed. These contents increased after storage were correlated with the reduction in activities of SOD and CAT. Seed deterioration of large seed (AGS190) was higher compared with small seeds (Cikurai and Willis). In experiment 3, seeds were harvested at harvest maturity (H1) which is 95% of the pods have reached mature brown color and 2-week delay after harvest maturity (H2). Except EC, delay harvest (H2) caused negative effects on the internal seed properties which reduced germination percentage, viability and vigor of seed and increased Phomopsis infection (ANOVA, P<0.05). No significantly different on the seedling growth of three varieties that harvested at H1 and H2 except root length of AGS190 harvested at H1 is longer than H2. The effect of non-dry seed (before drying), silica gel drying and oven-drying (40 oC) on seeds harvested from harvest maturity and 2 week delay harvest also studied. Germination percentage and EC of three varieties harvested at H1 are not significantly between non- and dried seed. Meanwhile, germination percentage, viability and vigor of dried AGS190 seed harvested at H2 lower than non-dry seed (before drying). This result is contrary with Cikurai and Willis. The finding also found that early seedling growth of dried 2-delay harvest seed lower than non-dry seed. As conclusion, maturity stage, storage condition and type of seed drying are the main factor to be counted to achieve the high germination, longevity and seedling growth and yield of soybean in Malaysian weather.